2008
DOI: 10.1303/jjaez.2008.13
|View full text |Cite
|
Sign up to set email alerts
|

Carrying and Transmission of Eremothecium coryli (Peglion) Kurtzman as a Causal Pathogen of Yeast-Spot Disease in Soybeans by Riptortus clavatus (Thunberg), Nezara antennata Scott, Piezodorus hybneri (Gmelin) and Dolycoris baccarum (Linnaeus)

Abstract: Carrying and Transmission of Eremothecium coryli (Peglion) Kurtzman as a Causal Pathogen of Yeast-Spot Disease in Soybeans by Riptortus clavatus (Thunberg), Nezara antennata Scott, Piezodorus hybneri (Gmelin) and Dolycoris baccarum (Linnaeus).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…coryli is transmitted by six species of pentatomid bugs (Daugherty 1967), but these species do not inhabit Japan. The four stink bug species found in Japan, R. clavatus, N. antennata, P. hybneri and D. baccarum, are known to carry and transmit E. coryli (Kimura et al 2008). In this study, E. ashbyi was also carried and transmitted by R. clavatus, suggesting that E. ashbyi is also transmitted by stink bugs after feeding on infected soybeans.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…coryli is transmitted by six species of pentatomid bugs (Daugherty 1967), but these species do not inhabit Japan. The four stink bug species found in Japan, R. clavatus, N. antennata, P. hybneri and D. baccarum, are known to carry and transmit E. coryli (Kimura et al 2008). In this study, E. ashbyi was also carried and transmitted by R. clavatus, suggesting that E. ashbyi is also transmitted by stink bugs after feeding on infected soybeans.…”
Section: Discussionsupporting
confidence: 52%
“…In this study, E. coryli and E. ashbyi were detected on an overwintering generation of R. clavatus. The carrying rates of E. coryli were approximated to the third generation of R. clavatus collected in late autumn 2006 (Kimura et al 2008). This result suggested that both yeasts overwinter in R. clavatus because the third generation of R. clavatus becomes the overwintering generation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Insects were surfacesterilized following the method of Kimura et al (2008a). The insects, sterilized cotton puffs soaked with sterile water and seeds of soybean cv.…”
Section: Microscopic Examination Of Field-collected Bugsmentioning
confidence: 99%
“…Recently, we proved that four true bug species, Riptortus pedestris (Fabricius) (=R. clavatus), Nezara antennata Scott, Piezodorus hybneri (Gmelin) and Dolycoris baccarum (Linnaeus), are associated with yeast spot in Japan (Kimura et al 2008a). In addition, E. ashbyi (Guilliermond ex Routien) Batra was shown to cause yeast spot and, E. coryli was transmitted by the true bug R. pedestris (Kimura et al 2008b).…”
Section: Introductionmentioning
confidence: 99%